Probabilistic Decision-Making in Children With Dyslexia - Pereira, Christa L. Watson; Zhou, Ran; Pitt, Mark A.; Myung, Jay I.; Rossi, P. Justin; Caverzasi, Eduardo; Rah, Esther; Allen, Isabel E.; Mandelli, Maria Luisa; Meyer, Marita; Miller, Zachary A.; Gorno Tempini, Maria Luisa (Frontiers in Neuroscience, 2022)
Background: Neurocognitive mechanisms underlying developmental dyslexia (dD) remain poorly characterized apart from phonological and/or visual processing deficits. Assuming such deficits, the process of learning complex tasks like reading requires the learner to make decisions (i.e. word pronunciation) based on uncertain information (e.g. aberrant phonological percepts)—a cognitive process known as probabilistic decision making, which has been linked to the striatum. We investigate 1) the relationship between dD and probabilistic decision-making and 2) the association between the volume of striatal structures and probabilistic decision-making in dD and typical readers. Methods: 24 children diagnosed with dD underwent a comprehensive evaluation and MRI scanning (3T). Children with dD were compared to age-matched typical readers (n=11) on a probabilistic, risk/reward fishing task that utilized a Bayesian cognitive model with game parameters of risk propensity ( γ^+) and behavioral consistency (β), as well as an overall adjusted score (average number of casts, excluding forced-fail trials). Volumes of striatal structures (caudate, putamen, and nucleus accumbens) were analyzed between groups and associated with game parameters. Results: dD was associated with greater risk propensity and decreased behavioral consistency estimates compared to typical readers. Cognitive model parameters associated with timed pseudoword reading across groups. Risk propensity related to caudate volumes, particularly in the dD group. Conclusion: Decision-making processes differentiate dD, associate with the caudate, and may impact learning mechanisms. This study suggests the need for further research into domain-general probabilistic decision-making in dD, neurocognitive mechanisms, and targeted interventions in dD.